Quality and Fatty Acid Composition of Lipids from Head of Indian Mackerel (Rastreliger kanagurta) and Tigertooth Croaker (Otolithes ruber) - Elavarasan, Krishnamoorthy; Kumar, Anuj; Tejpal, C. S.; Kumar, K. Sathish; Uchoi, Devananda; Ninan, George; Zynudheen, A. A. (Fishery Technology, 2017)
Fish processing discards contain valuable nutrients such as proteins, lipids and minerals. The lipid from mackerel and croaker head extracted by alkali solubilization was recovered and characterized for quality parameters such as peroxide value (PV), free fatty acid (FFA), thiobarbituric acid reactive substances (TBARS) and fatty acid composition. PV, FFA and TBARS values of lipids recovered from head of mackerel was higher than that of croaker. Both mackerel and croaker head lipids had higher amount of saturated fatty acids (SFA) and monounsaturated fatty acids (MUFA) and lower amount of polyunsatuarated fatty acids (PUFA) compared to fatty acids from muscle of the same fishes. Mackerel head lipids had higher PUFA content (30.81%) than that of croaker (18.71%). The SFA content was dominated by palmitic acid while the MUFA content was dominated by palmitoleic acid. Docosahexaenoic acid (DHA; C22: 6 Ï‰3) and Eicosapentaenoic acid (EPA; C 20: 5 Ï‰3) were the dominant PUFA in both the fish-head lipids. The study revealed the fish head waste as a potential source of Ï‰-3 fatty acids which can be recovered by alkali solubilization process.